Selma [videorecording (Blu-Ray)] - Oyelowo, David; Wilkinson, Tom, 1948-; Roth, Tim; Gooding, Cuba, Jr., 1968-; Winfrey, Oprah (Paramount, 2015)
Dr. Martin Luther King, Jr.'s historical struggle to secure voting rights for all people. A dangerous and terrifying campaign that culminated with an epic march from Selma to Montgomery, Alabama in 1964.